Planning of Wastewater Reuse Programme in Nigeria - Adewumi, James Rotimi; Oguntuase, Abiose Matthew (Consilience, 2016)
Despite the great awareness on the health and environmental implications of poorly disposed wastewater, the continuous pollution of the environment and surface water with wastewater generated from domestic, institutional and industrial activities in many Nigerian cities still remains a major concern. As population grows with rising standard of living more wastewater is generated and disposed to sensitive environments with negative impacts on the human and ecosystems. To promote sustainable and efficient wastewater management, global attention must be drawn towards wastewater reuse for both potable and non-potable uses. This paper presents baseline information on global wastewater reuse that can serve as a valuable guide on the integration of wastewater reuse in Nigeria as a component of National Integrated Water Resources Management.